Socio-Economic Barriers to The Adoption of Hygiene Behaviors for Stunting Prevention in Developing Countries: A Systematic Review - Ruth Rize Paas Megahati S; Liza Yuliana (RADINKA JOURNAL OF HEALTH SCIENCE, 2026)
Objective: This systematic review aims to identify and analyze the various socio-economic barriers that hinder the adoption of hygiene behaviors for stunting prevention. It specifically examines how economic factors, infrastructure limitations, and social norms influence the effectiveness of environmental health interventions in developing nations. Methods: A Systematic Literature Review (SLR) was conducted following the PRISMA protocol. Data were sourced from three primary databases: Scopus, Web of Science, and Google Scholar, covering the period from 2016 to 2024. A total of 24 research articles focusing on stunting dynamics and environmental factors in developing regions, including Indonesia, were selected for in-depth synthesis and analysis. Results: The findings reveal that systemic poverty, limited access to affordable clean water, and high operational expenses are the primary obstacles to hygiene practice. Additionally, the study identifies that maternal education level and household gender roles are significant determinants of the sustainability of these behaviors. The results underscore that hygiene education campaigns alone have a limited impact if the underlying economic and structural barriers remain unaddressed. Conclusion: Stunting prevention requires a multi-sectoral strategy that transcends purely medical and nutritional interventions. To be effective, policies must integrate household economic empowerment with the development of inclusive sanitation infrastructure. This study provides a critical perspective for policymakers to design interventions that are sensitive to the socio-economic constraints of communities in developing nations.